InSAR-based method for deformation monitoring of landslide source area in Baihetan reservoir, China - Liu, Meishan; Yang, Zhiquan; Xi, Wenfei; Guo, Junqi; Yang, Hong (Frontiers in Earth Science, 2023)
As a cascading disaster, the surge caused by the reservoir bank landslide seriously affects the stability of the reservoir bank and the dam body. In addition, large-scale hydropower projects are usually built in mountain and canyon areas with active geological structure movement, which provides rich material sources for the occurrence of landslides, so it is of great significance to monitor the deformation in the landslide source area of the reservoir. As science and technology have been leaping forward, a wide variety of high and novel technologies have been proposed, which can be adopted to monitor landslide deformation. It is noteworthy that InSAR is capable of monitoring target monitoring areas all time under all weathers without 2 the need to install any equipment. In this study, the time series deformation of the main landslide source area of the Baihetan reservoir after water storage was determined based on the time series InSAR method. The average annual deformation rate of the landslide source area of the Baihetan reservoir from April 2021 to January 2023 was determined by combining the Sentinel-1 SAR data of 55 ascending tracks and 46 descending tracks. Moreover, the vegetation cover variations from April 2021 to January 2023 in the study area were determined by combining the remote sensing data of Landsat8-9. A total of four typical source areas were selected based on the field investigation to analyze the deformation monitoring results and the vegetation cover variations. As indicated by the results: (1) After water storage, the slope deformation in all source areas was larger in the short term, and the deformation rate of the lower part turned out to be more significant, and the deformation rate exceeded 334.583mm/year. (2) On the steep slope, the effect of different types of vegetation on restraining deformation was different. The optimal effect was reported in shrubs, followed by grasslands, and the worst effect was reported in woodlands. The results of this study can provide scientific support for the prevention and control of regional geological disasters.